Lives Penciled in, the Reality of Chronic Health Conditions and Trauma: Reflexivity, Health, and Shadowed Identities - Hovey, Richard Bruce; Pavate, Veeresh; Vigouroux, Marie (Frontiers in Pain Research, 2022)
When living with chronic health conditions or experiences of trauma our lives ca become perpetually penciled-in. The use of penciled -in meaning to arrange out time tentatively, a date, an appointment, a meeting to see a movie or attend a class. Although, our technologically driven world of electronic calendars where everything is entered electronically the utility of the pencil and handwritten agendas have all but vanished. However, for the purpose of this article the pencil provides a metaphoric common ground to learn about the totality of the disruption experienced by living with chronic health conditions and trauma. The pencil is touchable, tangible and as a researcher and a person who lives with challenging health concerns, metaphors help me to create an understanding of the chaos of living a life in pain with cancer. This article is a person-centered account of the process of reflexive coping and self-processing of pain by a pain researcher and educator. This article focuses on the metaphor of penciled-in lives to provide a qualitative account of experiences of pain and trauma from chronic health issues both physical and emotional. This act of reflexivity becomes a personal examination of life. It reveals to me my beliefs, decisions, and practices prior and during of my hermeneutic journey and how these may have prejudiced my thinking and behaviours.